A Systematic Analysis of Hand Movement Functionality: Qualitative Classification and Quantitative Investigation of Hand Grasp Behavior - Liu, Yuan; Jiang, Li; Liu, Hong; Ming, Dong (Frontiers in Neurorobotics, 2021)
Understanding human hand movement functionality is fundamental in neuroscience, robotics, prosthetics, and rehabilitation. People are used to investigate the movement functionality separately from qualitative or quantitative perspectives. However, it is still limited to provide an integral framework from both perspectives with a logical manner. In this paper, we provide a systematic framework to qualitatively classify hand movement functionality, build prehensile taxonomy to explore the general influence factors of human prehension, and accordingly design the behavioral experiment to quantitatively understand the way of hand grasp. In qualitative analysis, two facts are explicitly proposed: 1) arm/wrist make a vital contribution to hand movement functionality; 2) the relative position (the relative position in this paper is defined as the distance between the center of human wrist and object center of gravity) is a general influence factor significantly impacting human prehension. In quantitative analysis, the significant influence of three influence factors contained object shape, size and relative position, is quantitatively demonstrated. As simultaneously considering the impact of relative position, object shape and size, the prehensile taxonomy and behavioral experiment results presented here should be more representative and complete to understand human grasp functionality. The systematic framework presented here is general and applicable to other body parts, such as wrist, arm etc. Finally, many potential applications and the limitations are clarified.